P032 Adequate health literacy predicts adherence to continuous positive airway pressure in adults with Obstructive Sleep Apnoea. (7th October 2021) - Ellender, C; Le Feuvre, S; Boyde, M; Winter, S; Duce, B; Hukins, C
Abstract: Study Objectives: Obstructive sleep apnoea (OSA) is a chronic disease with significant health implications and adequate adherence to continuous positive airway pressure (CPAP) is essential for effective treatment. In many chronic diseases, health literacy has been found to predict treatment adherence and outcomes. In this study, the aim was to determine the health literacy of a sleep clinic population and evaluate the association between health literacy and CPAP adherence. Methods: A prospective cohort study was undertaken, recruiting 104 consecutive patients with a variety of sleep diagnoses attending the clinic. The Short Form Rapid Estimate of Adult Literacy in Medicine (REALM-SF), a validated questionnaire was administered to measure health literacy. In a sub-group of 91 patients prescribed CPAP for OSA, CPAP usage was measured, with adequate usage defined as greater than 4hrs/night CPAP therapy. Results: 71% of the sleep clinic cohort was found to have adequate health literacy as measured by the REALM-SF. In those prescribed CPAP for OSA, inadequate health literacy was associated with a two fold increase risk for inadequate CPAP usage (adjusted odds ratio 2.75, 95% CI: 1.00 - 7.6, p = 0.05). There was a 1.7hr/night difference in median CPAP usage comparing those with adequate to inadequate health literacy (4.6hrs versus 6.3hrs/night). Conclusions: The majority of this sleep disorders cohort had adequate health literacy as measured by the REALM-SF questionnaire. However inadequate health literacy appears to be an independent predictor of treatment adherence, and may represent a potentially modifiable risk factor of poor treatment outcomes in OSA.